Upaya Meningkatkan Aktifitas Dan Hasil Belajar Mata Pelajaran Pendidikan Agama Islam Pada Pokok Bahasan Pelaksanaan Tata Cara Penyelenggaraan Jenazah Dengan Menggunakan Model Pembelajaran Koperatif Tipe NHT Siswa Kelas XI IPA 6 SMAN 3 Kotabumi - Rukmala mala (Eksponen, 2020)
The achievement of student learning outcomes today is still considered low, this is closely related to the conditions of teaching and learning activities that occur in class. To overcome this problem, there needs to be a change in the procedure for the teaching and learning process. One of the things that teachers can do is to apply the cooperative learning model type NHT. The research conducted on class XI IPA 6 SMAN 3 Kotabumi school year 2018-2019 is a classroom action research. The study was composed of 2 cycles with each cycle consisting of planning, implementing, observing and ending with reflection. In the first cycle it was carried out on the material for bathing and bathing the body and in the second cycle for the material for the body prayer. The results in this study indicate the use of the cooperative learning model type NHT on the subject of implementing the procedures for organizing a corpse can improve the learning outcomes of students in class XI IPA 6. Student learning outcomes have increased by 41% from cycle I to cycle II, while student activity has increased in the cycle. II where students are more disciplined, cooperative, polite and tolerant in learning. Thus the use of the NHT type cooperative learning model can improve the learning outcomes of MIPA 6 students.